Synthesis and biological evaluation of fentanyl acrylic derivatives. Issue 32 (5th April 2017) - Li, Shaohua; Cohen-Karni, Devora; Kovaliov, Marina; Tomycz, Nestor; Cheng, Boyle; Whiting, Donald; Averick, Saadyah
Abstract : Synthesis and biological evaluation of fentanyl acrylic derivatives. Abstract : The synthesis of novel fentanyl acrylate derivatives via bromo-fentanyl using Heck coupling is described. The synthesis is concise and represents an efficient and useful method for functionalizing fentanyl for medicinal chemistry investigations. The agonistic and analgesic activities are evaluated by Mu opioid receptor activation and hot plate assays in mice.